Cycles of Struggle in Biotechnology: Open Source Methods - Kipp, Margaret E. I. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
The open source methodologies used in software are interrogated and then compared to the methods used in farmers' rights groups. The use of open source methods in other contexts illustrates increasing interest in grassroots democratic movements participating in the continuing process of balance between public and private interests. These efforts provide a possible alternate framework for policy decisions concerning intellectual property. Les méthodologies de source libre utilisées par les logiciels sont observées et ensuite comparées aux méthodes utilisées par les groupes de droits des agriculteurs. L’utilisation des méthodes de source libre dans divers contextes illustre l’intérêt croissant des mouvements démocratiques de masses participant au processus continu de l’équilibre entre les intérêts publics et privés. Ces efforts présentent une structure alternative possible pour les décisions stratégiques au sujet de la propriété intellectuelle.